2014
DOI: 10.1111/ijd.12633
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of sarcoidosis in Afro‐Caribbean people: a 7‐year retrospective study in Guadeloupe

Abstract: This epidemiological study on sarcoidosis in Guadeloupe reveals a low incidence of the disease and a high degree of severity as evidenced by the average number of affected organs, the high frequency of extrathoracic organ involvement, the frequent use of corticosteroids, and a mortality rate of 5.3%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 11 publications
3
15
3
Order By: Relevance
“…In this study of the epidemiology of sarcoid arthropathy in a geographically well‐defined population, joint pain was a relatively common clinical manifestation, seen in 12% of patients with sarcoidosis. This frequency is consistent with previous population‐based studies that observed articular symptoms in 6–22% of patients . However, the current study is the first population‐based study to describe the detailed clinical characteristics of sarcoid arthropathy.…”
Section: Discussionsupporting
confidence: 92%
“…In this study of the epidemiology of sarcoid arthropathy in a geographically well‐defined population, joint pain was a relatively common clinical manifestation, seen in 12% of patients with sarcoidosis. This frequency is consistent with previous population‐based studies that observed articular symptoms in 6–22% of patients . However, the current study is the first population‐based study to describe the detailed clinical characteristics of sarcoid arthropathy.…”
Section: Discussionsupporting
confidence: 92%
“…The age distribution of subjects with sarcoidosis in our study was similar to that of subjects in Western studies [ 3 , 27 , 28 ], which show a monophasic pattern, and was unlike that of Japanese and Scandinavian subjects, which show a biphasic distribution [ 11 , 29 ]. On the other hand, the age distribution of males in the present study showed a bimodal pattern due to the presence of a younger peak in the age group 30–39 years that was distinct from that seen in Western populations with a single incidence peak in aged 40–59 years [ 3 , 12 , 30 ]. In a previous Korean study, the peak age of sarcoidosis in males was in their thirties [ 15 ], but the present study confirmed the second peak between ages 60–69 years.…”
Section: Discussioncontrasting
confidence: 76%
“…The annual incidence rate in Japan is low (1–2 in 10 5 population at risk) and appears to have a bimodal age distribution, with one peak at ages 25–34 years and another at ages 60–64 years [ 8 , 11 ], while Western countries showed a single incident peak at 55–64 years [ 9 ]. Sarcoidosis usually occurs more frequently in females [ 8 , 10 12 ], but male predominance has been observed in Northern Europe [ 7 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study yielded an average annual incidence of 2.28 per 100,000 and prevalence of 21.09 per 100,000. 24…”
Section: North Americamentioning
confidence: 99%